Black/Africana Communication Theory (Springer International Publishing, 2018)
Most Western-driven theories do not have a place in Black communicative experience, especially in Africa. Many scholars interested in articulating and interrogating Black communication scholarship are therefore at the crossroads of either having to use Western-driven theory to explain a Black communication dynamic, or have to use hypothetical rules to achieve their objectives, since they cannot find compelling Black communication theories to use as reference. Colonization and the African slave trade brought with it assimilationist tendencies that have dealt a serious blow on the cognition of most Blacks on the continent and abroad. As a result, their interpersonal as well as in-group dialogic communication had witnessed dramatic shifts. Black/Africana Communication Theory assembles skilled communicologists who propose uniquely Black-driven theories that stand the test of time. Throughout the volume's fifteen chapters theories including but not limited to Afrocentricity, Afro-Cultural Mulatto, Venerative Speech Theory, Africana Symbolic Contextualism Theory, HaramBuntu-Government-Diaspora Communications Theory, Consciencist Communication Theory and Racial Democracy Effect Theory are introduced and discussed. Kehbuma Langmia is Professor/Chair and Fulbright Scholar in the Department of Strategic, Legal and Management Communications, Howard University in Washington, DC, USA. He has extensive knowledge and expertise in Public Speaking, Information Communication Technology (ICT), Intercultural Communication and Social Media. He has published eleven books, fourteen book chapters and nine peer-reviewed journal articles nationally and internationally. He is the recipient of the 2017 Toyin Falola Book Award for his most recent book, Globalization and Cyberculture (Palgrave 2016).